The importance of teaching Libras from early childhood education: a matter of social inclusion (Research, Society and Development, 2021)
This article aimed to describe the importance of teaching Brazilian Sign Language - Libras since early childhood education. For this, a historical analysis of the evolution of the teaching of Libras in Brazilian education was carried out, as well as of the Legislation that focuses on guaranteeing the inclusive education of students with deafness in the country. In addition to verifying public educational policies aimed at special education. In this sense, the teaching of Libras, despite being guaranteed by national laws, shows a series of difficulties in schools, especially in the early grades, due to the lack of sign language interpreters in the classroom. In the methodological part of this scientific work, bibliographical and documental research of an applied nature was used, using the deductive method and the qualitative approach. Thus, the research concluded that the teaching of Libras, although it is standardized in schools, needs effective public policies aimed at special education, in order to guarantee the protection of the often excluded minority.